Stable hydrogen isotopes of isoprenoids and n-alkanes as a proxy for estimating the thermal history of sediments through geological time - Maslen, Ercin; Grice, Kliti; Dawson, Daniel; Wang, Sue; Horsfield, B. (SEPM Society for Sedimentary Geology, 2013)
The effect of thermal maturation on the δD values of individual petroleum hydrocarbons (n-alkanes and regular isoprenoids) from sedimentary organic matter over geological timescales has been explored in six different sedimentary sequences covering a wide range of maturities; i.e., 0.53% – 1.6% vitrinite reflectance (R o or equivalent; i.e., Re , Rc ). These include new data and recently reported literature data on formations ranging in age from the Early Cretaceous to the Permian. The application of Deuterium/Hydrogen (D/H) of biomarkers as a maturity proxy for Devonian source rocks from the Western Canada Sedimentary Basin is also presented here, extending this application to much older sediments than previously studied. In each case, pristane and phytane are predominantly derived from the lipid side chain of chlorophyll a present in most photosynthetic organisms, with an additional (but minor) contribution to pristane from tocopherol of land plants in selected cases. The n-alkanes represent contributions of algae, bacteria, and in certain cases higher plants. In general, the n-alkanes, pristane, and phytane from relatively immature sediments have δ D values that retain the isotopic signature of their natural product precursors; i.e., biosynthesized lipid components made up of acetyl and isoprene subunits, respectively. With increasing maturity, pristane and phytane become more enriched in deuterium (D), while the n-alkanes generally remain at a constant isotopic composition until an overmature level is reached, at which point there is a significant enrichment of D in n-alkanes. The enrichment of D in pristane and phytane with increasing maturity correlates strongly with changes in traditional maturity parameters, including vitrinite reflectance, Tmax, and molecular parameters, providing evidence that D enrichment is associated with thermal maturation.